Energy and Exergy Analysis of Drying Behavior for a Fish - Erdem, Murat; Kamisli, Fethi; Varol, Yasin; Öztop, Hakan Fehmi (My University, 2021)
The drying of rainbow trout in a square cross-sectional drier is examined to analyze the system in terms of energy and exergy by considering a thin-layer drying approach. In the experiments, the inlet velocity of air was kept to be constant at 1.5 m/s while varying the temperature of inlet air of 38, 46, and 53 ?C with relative moisture ranged from 28 to 43 percent. In the beginning, the moisture content of specimen (fish) on wet basis was found to be around 75 %. Fish with an average weight of 200 grams were used in the experiments. The energy analysis on the consumed energy for the drying process was performed by considering the energy balance. Moreover, the exergy analysis was actualized by considering the second law of thermodynamics to identify the efficiency of the device and the magnitude of energy losses. At the beginning of the drying, the energy consumption was high on account of the large moisture content and decreased with decreasing moisture content. The exergy for inflow and outflow was observed to be increased with increasing the air temperature used for the drying process. Furthermore, it was observed that the lower temperature of the drying air, the lower exergy losses for the entire drying period in the range of 0-900 minutes.
Keywords: Ekserji; Enerji; Taşınımlı kurutucu